The effectiveness of the "ANIMO" educational model using traditional games to improve vegetable and fruit consumption behavior in adolescents - Kalsum, Ummi; Saputra, Nofrans Eka; Syamsurizal; Handayani, Irma (Proceedings Academic Universitas Jambi, 2025)
Background: Consumption of vegetables and fruits in adolescents is still very low, especially at the age of 10-14 years which only reaches 0.36%. Teenagers tend to prefer fast food such as sausages, hamburgers, and meatballs to eating vegetables and fruits. Objective: This study aims to determine the effectiveness of the traditional game-based "ANIMO" educational model in improving vegetable and fruit consumption behavior in adolescents. Methods: The study used a quasi-experimental design with a two-group pre-test post-test design. The research locations were SMPN 6 Jambi City as the intervention group (n=52) and SMPN 11 Jambi City as the control group (n=51). Data analysis used the Wilcoxon test to see changes in the group and the Mann-Whitney test to see the differences between groups. Results: The Wilcoxon test showed a significant increase in vegetable and fruit consumption behavior in the intervention group (p=0.000), while the control group showed no significant change (p=0.188). The Mann-Whitney test showed that there was no significant difference between the two groups at the pre-test time (p=0.013), but there was a significant difference after the intervention (p=0.001). Conclusion: The traditional game-based "ANIMO" educational model was effective in improving vegetable and fruit consumption behavior in adolescents. This model is recommended to be implemented in health education in schools and health care facilities to support the improvement of healthy nutritional behavior in adolescents.